Fundamental soil science - Coyne, Mark S. (Thomson Delmar Learning, 2006)
Fundamental Soil Science teaches students about the many facets and uses of soil beyond its use as an agricultural resource. The authors take the approach that soils are dynamic, living, natural resources that affect every aspect of our lives. They also put particular focus on those areas of soil science they deem most critical, including physical, chemical and biological properties. As a learning tool, this publication introduces the reader to concepts then reinforces them throughout. As a reference tool, it meets professionals needs when they seek information about basic soil concepts pertinent to practical experience.